Kembara UMP Prihatin serves Kapit community - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KAPIT, 24 August 2022 - Kembara Prihatin Universiti Malaysia Pahang (UMP) organised by Yayasan UMP in collaboration with Institut Kemahiran MARA (IKM), Bintulu successfully realised the concept of #KeluargaMalaysia when 52 volunteers served the community of Rumah Panjang Diau Anak Lumut Pulau Raya in Kapit from 19 to 25 August 2022.